2012
DOI: 10.1107/s1600536812023975
|View full text |Cite
|
Sign up to set email alerts
|

KMg0.09Fe1.91(PO4)2

Abstract: KMg0.09Fe1.91(PO4)2, potassium [iron(II)/magnesium] iron(III) bis(orthophosphate), is a solid solution derived from compounds with general formula KM IIFe(PO4)2 (M II = Fe, Cu), in which the Mg atoms substitute Fe atoms only in the octa­hedrally surrounded sites. The framework of the structure is built up from [FeO5] trigonal bipyramids and [MO6] (M = (Fe, Mg) octa­hedra sharing corners and edges and connected by two types of bridging PO4 tetra­hedra. The K+ cations are nine-coordinated and are situated in cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…For rubidium iron phosphates, see: Hidouri et al (2010). The title compound is isostructural with KCuFe(PO 4 ) 2 (Badri et al, 2011) and K(Fe,Mg)(PO 4 ) 2 (Yatskin et al, 2012). For P-O distances in monophosphate groups, see: Baur (1974).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For rubidium iron phosphates, see: Hidouri et al (2010). The title compound is isostructural with KCuFe(PO 4 ) 2 (Badri et al, 2011) and K(Fe,Mg)(PO 4 ) 2 (Yatskin et al, 2012). For P-O distances in monophosphate groups, see: Baur (1974).…”
Section: Related Literaturementioning
confidence: 99%
“…This compound is isostructural with KCuFe(PO 4 ) 2 (Badri et al, 2011) and K(Fe,Mg)(PO 4 ) 2 (Yatskin et al, 2012). The structure consists of a three-dimensional assemblage of Cu 2 O 8 units of edge-sharing CuO 5 trigonal bipyramids, linked to each other by FeO 6 octahedra through common corners to form crossing zigzag chains that run parallel to the [011] and…”
Section: Crystal Datamentioning
confidence: 99%
“…Indeed, magnesium phosphate displays a bi-dimensional structure, built up from layers of corner-sharing (Fe,Mg)O 4 and PO 4 tetrahedra, the K + cations being located within the interlayer space. By contrast, the structure of copper phosphate is three-dimensional, built up by crossing chains of Cu 2 O 8 units, alternating with FeO 6 octahedra; the K + ions are found in one-dimensional hexagonal tunnels running along the [ [9] and KM II Fe(PO 4 ) 2 (M II = Co, Ni) [10]. In addition, the structural characterization revealed that the first compound was isotypic with KM II Fe(PO 4 ) 2 (M II = Cu, Fe) [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, M.M. Yatskin et al have reported the formation of three new compounds: KMg 0.09 Fe 1.91 (PO 4 ) 2 [ 9 ] and KM II Fe(PO 4 ) 2 (M II = Co, Ni) [ 10 ]. In addition, the structural characterization revealed that the first compound was isotypic with KM II Fe(PO 4 ) 2 (M II = Cu, Fe) [ 8,11 ].…”
Section: Introductionmentioning
confidence: 99%